2020
DOI: 10.2217/fca-2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

How Well do We Represent Ourselves: an Analysis of Cardiology Fellowships Website Content

Abstract: Background: The Internet is the primary source of information for prospective cardiology fellowship aspirants. The objective of this study was to evaluate cardiology fellowship programs' online profile. Materials & methods: Two independent reviewers accessed 221 US based cardiology fellowship program websites obtained through Fellowship and Residency Electronic Interactive Database for pre-selected 20 criteria. The update status of websites was assessed using 6-point criteria. Results: Only 25 (11.3%) webs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 8 publications
3
31
1
Order By: Relevance
“…As medical school applicants apply to, interview at, and ultimately decide which institution to attend, careful planning and research is essential. The internet is easily accessible and multiple studies have shown the importance of websites in recruitment for residency, 5,8,9 which likely applies to students applying for medical school as well. This will likely be of growing importance in the wake of the COVID-19 pandemic, as in-person methods of evaluating prospective institutions are being replaced with virtual means.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As medical school applicants apply to, interview at, and ultimately decide which institution to attend, careful planning and research is essential. The internet is easily accessible and multiple studies have shown the importance of websites in recruitment for residency, 5,8,9 which likely applies to students applying for medical school as well. This will likely be of growing importance in the wake of the COVID-19 pandemic, as in-person methods of evaluating prospective institutions are being replaced with virtual means.…”
Section: Discussionmentioning
confidence: 99%
“…As the data contained in residency websites can be subjective, we created a standardized process to evaluate the websites, similar to the previous studies in other specialties. [4][5][6][7][8] First, we only searched for the presence or absence of items, with no attempt made to grade the quality or accuracy of the content. Second, any information that was not directly listed on medical school website was excluded, such as links to external materials or websites, which usually contained general, non-speci c information rather than medical school-speci c information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology for this study was developed from several recently published program website analysis studies [2][3][4][5][6]. Our study did not incorporate the use of human or animal subjects and used publicly available information on the internet.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have evaluated the quality and comprehensiveness of program websites in different medical subspecialties [2][3][4]. All of the studies concluded that residency and fellowship websites have significant room for improvement despite their vital role in the decision-making process.…”
Section: Introductionmentioning
confidence: 99%